A suspected case of COVID-19 vaccine (Covishield) induced Guillain Barre syndrome-a case report - Gupta, Anirudh; Verma, S. L.; Rana, Dinesh; Goel, Varnik (International Journal of Advances in Medicine, 2022)
Guillain Barre syndrome (GBS) is a collection of clinical syndromes that manifest as an acute inflammatory poly radiculopathy. It usually presents as an acute, non-febrile, monophonic, post infectious illness manifesting as ascending weakness and areflexia. It is an autoimmune disorder characterized by production of antibodies against the myelin and is often triggered by bacterial and viral infections, vaccines against rabies, flu and COVID-19. Here we present a case of 31 years old male with characteristic signs and symptoms of GBS possibly triggered by Covishield vaccine.